Changes in the distribution of wealth in China, 1995 - 2002 - Shi Li; Renwei Zhao (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
his paper investigates some major changes in the wealth distribution in China using the data from two national household surveys conducted in 1995 and 2002. The surveys collected rich information on household wealth and its components, enabling a detailed analysis of changes in wealth distribution among Chinese households. Our analysis indicates that the wealth distribution in China as a whole became much more unequal in 2002 than it was in 1995. The housing reform, in which public apartments were sold to urban households at extremely low prices, has accelerated the accumulation of wealth among urban households on the one hand, and widened the wealth gap between urban and rural areas on the other.
Keywords: D3; E2; 330; China; wealth; income; distribution; inequality; households; Vermögensverteilung; Privater Haushalt; China